1985
DOI: 10.1254/jjp.38.419
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Enalapril on Blood Pressure, Stroke, Plasma Renin, Urinary Electrolytes and PGE2 Excretion in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Abstract-Antihypertensive effect of enalapril (MK-421

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The antihyper tensive potency of these CE inhibitors in SHRSP rats is compatible with that found in our previous study (10). Urinary excretion of kinins during treatment with CE inhibitors is shown in Fig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The antihyper tensive potency of these CE inhibitors in SHRSP rats is compatible with that found in our previous study (10). Urinary excretion of kinins during treatment with CE inhibitors is shown in Fig.…”
supporting
confidence: 90%
“…In a previous study in 14 to 15 -week old SH RSP rats, we found significant decreases in urinary excretion of kinins and urine volume (UV) in the 5th and 10th weeks of treatment with both enalapril and captopril (10). However, the data on urinary kinin excretion were not included in the paper because we collected acidified urine samples without pepstatin A, and the pos sibility of kinin formation during urine collection could not be excluded.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…22 - 23 The renin-angiotensin system also participates in the pathophysiology of malignant hypertension in SHRSP, as shown by previous reports. 24 - 26 However, previous research done on the renin-angiotensin system of SHRSP has been limited to the circulating system. 22 -24 -26 -mating at Santen Pharmaceutical Co., Ltd., Osaka, Japan.…”
mentioning
confidence: 99%
“…Consecutive dosing of enalapril at 10 mg/kg, p.o. produced a sustained antihypertensive effect in SHRSP rats (11).…”
Section: Procedures In Animalsmentioning
confidence: 89%